Development and optimization of tablea-pili nut spread using mixture response surface methodology - Benig, John Bhenz R.; Francisco, Maria Leonora d.L. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Mixture response surface methodology was utilized to determine the optimal formulations for tablea-pili nut spread. Sixteen formulations, comprised of varying levels of pili nut (25-90%), tablea syrup (5-70%) and sugar (5-55%), were generated using a D-optimal mixture design and were prepared for a consumer acceptance test. Using a 9-point Hedonic scale, response variables including color, aroma, spreadability, sweetness, flavor and overall acceptability of the samples were evaluated by the panelists. Response surface models for each attribute were obtained and tested for analysis of variance (ANOVA). Results showed that all models were significant (p<0.05) hence all models were superimposed to generate an overlay plot containing the optimal region of spread formulations. A combination of components with 32-57% pili nut, 27-49% tablea and 7-32% sugar was determined to be optimum formulations which could attain a consumer acceptance rating of ≥6.00 for all attributes. Validation of the models, using optimal and non-optimal formulations, indicated that models were valid since majority of the attributes showed no significant difference between actual and predicted sensory mean scores. Further studies on each raw material used may be done to understand the effects of their interactions on the final product. Lastly, a physicochemical analysis of the product can help to determine the correlation of physicochemical properties to sensory responses of the consumers.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Pili nut; Tablea-pili.